Electrical remodeling of atrioventricular junction: a study on retrogradely perfused chick embryonic heart - Zabrodska, Eva; Kvasilova, Alena; Sedmera, David; Olejnickova, Veronika (American journal of physiology. Heart and circulatory physiology, 2024)
Atrioventricular (AV) accessory pathways (APs) provide additional electrical connections between the atria and ventricles, resulting in severe electrical disturbances. It is generally accepted that APs originate in the altered annulus fibrosus maturation in the late prenatal and perinatal period. However, current experimental methods cannot address their development in specific locations around the annulus fibrosus because of the inaccessibility of late fetal hearts for electrophysiological investigation under physiological conditions. In this study, we describe an approach for optical mapping of the retrogradely perfused chick heart in the last third of the incubation period. This system showed stability for electrophysiological measurement for several hours. This feature allowed analysis of the number and functionality of the APs separately in each clinically relevant position. Under physiological conditions, we also recorded the shortening of the AV delay with annulus fibrosus maturation and analyzed ventricular activation patterns after conduction through APs at specific locations. We observed a gradual regression of AP with an area-specific rate (left-sided APs disappeared first). The results also revealed a sudden drop in the number of active APs between embryonic days 16 and 18. Accessory myocardial AV connections were histologically documented in all positions around the annulus fibrosus even after hatching. The fact that no electrically active AP was present at this stage highlights the necessity of electrophysiological evaluation of accessory atrioventricular connections in studying AP formation.NEW & NOTEWORTHY We present the use of retrograde perfusion and optical mapping to investigate, for the first time, the regression of accessory pathways during annulus fibrosus maturation, separately examining each clinically relevant location. The system enables measurements under physiological conditions and demonstrates long-lasting stability compared with other approaches. This study offers applications of the model to investigate electrical and/or functional development in late embryonic development without concern about heart viability.
Keywords: atrioventricular accessory pathway; Langendorff perfusion; nodus atrioventricularis; kuřecí embryo; zvířata; akční potenciály; perfuze; Perfusion; Atrioventricular Node; preexcitation; Action Potentials; Chick Embryo; Animals